Emerging insights into nitrogen assimilation in gymnosperms. - Valderrama-Martín, José Miguel; Ortigosa Peña, Francisco; Ruiz-Canton, Francisco Javier; Ávila-Sáez, Concepción; Cañas-Pendón, Rafael Antonio; Cánovas-Ramos, Francisco Miguel (Springer Nature, 2023)
Gymnosperms are a heterogeneous and ancient group of seed plants that includes conifers, ginkgos, cycads and gnetophytes. Molecular studies on extant gymnosperms have been constrained by some discouraging features for experimental research such as their long life cycles, large sizes, complex megagenomes and abundant phenolic compounds in their woody tissues. However, the development of high-throughput sequencing and refined multiomics technologies in the last few years has allowed to explore the molecular basis of essential processes in this ancient lineage of plants. Nitrogen is one of the main limiting factors determining vascular development and biomass production in woody plants. Therefore, nitrogen uptake, metabolism, storage and recycling are essential processes for fundamental gymnosperm biology. Here, recent progress in the molecular regulation of nitrogen assimilation in gymnosperms is reviewed and some future perspectives on this topic are outlined.
Keywords: Gimnospermas; Plantas - Efectos del nitrógeno; Nitrogen; Assimilation; Gymnosperms